2014
DOI: 10.5194/isprsarchives-xl-8-163-2014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Temporal and Spatial Dynamics of the Dengue Epidemic in Northern Sri Lanka

Abstract: ABSTRACT:Dengue outbreaks are affected by biological, ecological, socio-economic and demographic factors that vary over time and space. These factors have been examined separately, with limited success, and still require clarification. The present study aimed to investigate the spatial and temporal relationships between these factors and dengue outbreaks in the northern region of Sri Lanka.Remote sensing (RS) data gathered from a plurality of satellites: TRMM TMI, Aqua AMSR-E, GCOM-W AMSR2, DMSP SSM/I, DMSP SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This review analyses studies providing evidence on many climate variables. The majority of the articles which have studied the effect of temperature on dengue incidence have concluded that there is a positive association between moderate temperature between 25 0 C -34 0 C and dengue incidence (Ajim Ali & Ahmad, 2018;Ali et al, 2020;Anno et al, 2014;Anwar et al, 2019;Arcari & Tapper, 2017;Arsin et al, 2020;Campbell, 2014;Haryanto, 2016;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, & Murhekar, 2020;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, Murhekar, et al, 2020;Khalid et al, 2021;Lowe et al, 2016;Netrananda & Mani, 2021;Polwiang, 2016;Roy et al, 2018;Salamah et al, 2012;Salim & Syairaji, 2020;Sriklin et al, 2021) . One study has shown the negative association between maximum temperature and dengue incidence (S Wongkoon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review analyses studies providing evidence on many climate variables. The majority of the articles which have studied the effect of temperature on dengue incidence have concluded that there is a positive association between moderate temperature between 25 0 C -34 0 C and dengue incidence (Ajim Ali & Ahmad, 2018;Ali et al, 2020;Anno et al, 2014;Anwar et al, 2019;Arcari & Tapper, 2017;Arsin et al, 2020;Campbell, 2014;Haryanto, 2016;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, & Murhekar, 2020;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, Murhekar, et al, 2020;Khalid et al, 2021;Lowe et al, 2016;Netrananda & Mani, 2021;Polwiang, 2016;Roy et al, 2018;Salamah et al, 2012;Salim & Syairaji, 2020;Sriklin et al, 2021) . One study has shown the negative association between maximum temperature and dengue incidence (S Wongkoon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown the negative association between maximum temperature and dengue incidence (S Wongkoon et al, 2013). Most of the articles which have studied the relationship between the number of rainy days and dengue cases have shown a strong significant relationship (Gama & Nakagoshi, 2013;(Ali & Ma'Rufi, 2018;Anno et al, 2014); (Chandran & Azeez, 2015) ; Ali & Ma'Rufi, 2018;Rahman et al, 2018;Ummi Khairunisa & Wahyuningsih, 2018;Ishak & Kasman, 2018;Tosepu et al, 2018;Supadmi et al, 2019;(Minarti et al, 2021;S. A. Rahman et al, 2018;Rusli & Yushananta, 2020) Nair & Aravind, 2020Minarti et al, 2021;(Dutta et al, 2021); (Ishak & Kasman, 2018;Ummi Khairunisa & Wahyuningsih, 2018;Nair & Aravind, 2020;Sriklin et al, 2021;Supadmi, Perwitasari, Abdulah, & Suwantika, 2019;Tosepu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the moment there are no universal models that would make it possible to effectively make such forecasts for various territories. There are separate studies (Anno, et al 2014, Kiang, Soebiyanto, 2012, Naish, Tong, 2014, Chan, et al, 2011 describing forecast models for certain territories, but the impossibility of extrapolating the results of these works to other territories significantly reduces their usefulness (The Influence of Global Environmental Change on Infectious Disease Dynamics, 2014, Gubler, 2011).…”
Section: Introductionmentioning
confidence: 99%